Experimental Study on Effects of Adipose-Derived Stem Cell–Seeded Silk Fibroin Chitosan Film on Wound Healing of a Diabetic Rat Model. Issue 5 (May 2018) - Wu, Yan-Yun; Jiao, Yan-Peng; Xiao, Li-Ling; Li, Min-Min; Liu, Hong-Wei; Li, Sheng-Hong; Liao, Xuan; Chen, Yong-Tian; Li, Jiang-Xuan; Zhang, Yang
Abstract : Background: Wound healing is a complex process that relies on growth factors and stimulation of angiogenesis. Tissue engineering materials composed of adipose-derived stem cells (ADSCs) and silk fibroin (SF)/chitosan (CS) may be able to solve this problem. The aim of this study was to investigate the wound-healing potential of ADSC-seeded SF/CS in streptozotocin-induced diabetic rats. Materials and Methods: Thirty-six male Sprague-Dawley rats were purchased and randomly assigned into 3 groups: a control group (no graft), a group treated with SF/CS film graft, and a group treated with ADSC-seeded SF/CS graft. The number of animals in each group was 12. Diabetes was induced by an intraperitoneal injection of streptozotocin. A cutaneous wound was incised at the dorsal region of all the experimental animals. The ADSCs were labeled with CM-Dil fluorescent staining. Wound healing was assessed for all animal groups by observing the rate of wound closure and hematoxylin and eosin staining. The expression of epidermal growth factor, transforming growth factor-β, and vascular endothelial growth factor at the wound sites was studied by enzyme-linked immunosorbent assay to evaluate the effect of growth factors secreted by ADSCs. The differentiation of ADSCs was analyzed by immunofluorescence staining. Results: The ADSC-seeded SF/CS film treatment significantly increased the rates of wound closure in treated animals, and hence wound healing was drastically enhanced for ADSC-SF/CS treatment groups compared with control groups and SF/CS film treatment group. Histological observations showed the condition of wound healing. Enzyme-linked immunosorbent assay and immunofluorescence staining observations showed the secretion and differentiation of ADSCs, respectively. Conclusions: Our analyses clearly suggested that it is feasible and effective to enhance wound healing in a diabetic rat model with ADSC-seeded SF/CS film.